Proceedings of the Aristotelian Society - Aristotelian Society (Great Britain); EBSCO Publishing (Firm); JSTOR (Organization) (London : Williams and Norgate, 1942)
The proceedings of the Aristotelian Society contains the papers read at the Society's fortnightly meetings in London throughout the academic year.
Imprint varies.
Mode of access: World Wide Web.
Description based on: Vol. 1, no. 1 1888; title from cover (JSTOR, viewed July 28, 2008).
Latest issue consulted: Vol. 108, no. 1, pt. 2 (Aug. 2008) (Blackwell Synergy, viewed July 22, 2008).
Keywords: Aristotelian Society (Great Britain) -- Periodicals; Aristotelian Society (Great Britain); Aristotelian Society (Great Britain); Philosophy -- Periodicals; Philosophy; Periodicals